2019
DOI: 10.1158/0008-5472.can-18-0614
|View full text |Cite
|
Sign up to set email alerts
|

WWOX Inhibits Metastasis of Triple-Negative Breast Cancer Cells via Modulation of miRNAs

Abstract: Triple-negative breast cancer (TNBC) is a heterogeneous, highly aggressive, and difficult to treat tumor type. The tumor suppressor WWOX spans FRA16D, a common fragile site that is commonly altered in breast cancer. Despite recent progress, the role of WWOX in TNBC metastasis is unknown. Here we report that WWOX inactivation correlates with advanced stages of TNBC and that its levels are frequently altered in TNBC cells. Ectopic restoration of WWOX in WWOX-negative TNBC cells inhibited metastasis while its dep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 49 publications
3
42
0
Order By: Relevance
“…[35][36][37] Our recent observations demonstrated that WWOX can regulate the levels of several miRNAs, which regulates TNBC metastasis. 34 In particular, we showed that WWOX could regulate the c-MYC/miR-146a/Fibronectin axis to antagonize TNBC invasion and tumor growth. 33,34 In other reports, it has been proposed that WWOX loss promotes metastasis of TNBC cells through regulating the JAK2/STAT3 axis, 38,39 further emphasizing the role of WWOX in antagonizing tumorigenesis.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…[35][36][37] Our recent observations demonstrated that WWOX can regulate the levels of several miRNAs, which regulates TNBC metastasis. 34 In particular, we showed that WWOX could regulate the c-MYC/miR-146a/Fibronectin axis to antagonize TNBC invasion and tumor growth. 33,34 In other reports, it has been proposed that WWOX loss promotes metastasis of TNBC cells through regulating the JAK2/STAT3 axis, 38,39 further emphasizing the role of WWOX in antagonizing tumorigenesis.…”
Section: Introductionmentioning
confidence: 87%
“…34 In particular, we showed that WWOX could regulate the c-MYC/miR-146a/Fibronectin axis to antagonize TNBC invasion and tumor growth. 33,34 In other reports, it has been proposed that WWOX loss promotes metastasis of TNBC cells through regulating the JAK2/STAT3 axis, 38,39 further emphasizing the role of WWOX in antagonizing tumorigenesis. Moreover, a recent study showed that WWOX-deficient metastatic cells actively evade WWOX positive cells in their environment and then utilize various signaling pathways in order to force WWOX positive cells to undergo apoptosis, allowing further progression of metastasis.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…The FOXP3/miR-146/NF-kB axis limits tumour growth and could be a valuable target for therapy [200]. The role of miR-146a includes the reduction of fibronectin and opposing to the epithelial phenotype in TNBC subtype with a pro-metastatic activity supported via the oncosuppressor WWOX, that antagonizes MYC functions [201].…”
Section: Other Non-coding Rnas Relevant In Breast Cancermentioning
confidence: 99%